2009
DOI: 10.1017/s1751731109990693
|View full text |Cite
|
Sign up to set email alerts
|

Pig meat quality from entire males

Abstract: This paper constitutes an updated review of the production and meat quality aspects of rearing entire male pigs. Since a major obstacle in rearing entire males is the incidence of boar taint, possible methods for detection are also summarised. Safe and fast methods for detection of boar taint would be valuable in avoiding complaints from consumers. Pig meat quality is determined by many aspects, among which odour and taste are the most important attributes. Odour may be negatively affected by the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 53 publications
2
94
1
6
Order By: Relevance
“…A similar effect was observed with EM compared with SCM, although EM have consistently higher meat percentages and the effect of basal lean meat percentage is less pronounced. These observations are in line with the studies conducted by Lundstrom et al, (2009) and Bonneau (1998) who indicated that the advantage of lean meat growth when shifting towards EM pigs may have decreased because of selection for leaner pig breeds. None of the studies on the interaction between genotype and castration method on carcass quality published thus far showed any significant interactions (D'Souza and Mullan, 2003;Morales et al, 2011 and.…”
Section: Aluwé Tuyttens and Milletsupporting
confidence: 90%
“…A similar effect was observed with EM compared with SCM, although EM have consistently higher meat percentages and the effect of basal lean meat percentage is less pronounced. These observations are in line with the studies conducted by Lundstrom et al, (2009) and Bonneau (1998) who indicated that the advantage of lean meat growth when shifting towards EM pigs may have decreased because of selection for leaner pig breeds. None of the studies on the interaction between genotype and castration method on carcass quality published thus far showed any significant interactions (D'Souza and Mullan, 2003;Morales et al, 2011 and.…”
Section: Aluwé Tuyttens and Milletsupporting
confidence: 90%
“…Finishing intact boars can be an economically advantageous alternative to surgical castration (de Roest et al, 2009;Lundströ m et al, 2009). Because of the high heritability of boar taint compounds, breeding is an excellent tool to reduce the number of tainted carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory analysis can be used to reveal the concentration of skatole, indole and androstenone in fat. A variety of methodologies has been developed for this purpose, for example, methods based on HPLC, GC and LC-MS, as well as immunological and colorimetric methods (Zamaratskaia, 2004;Lundströ m et al, 2009;Haugen et al, 2012). Concentrations of skatole and androstenone are also, but less frequently, analysed in matrices other than fat, such as serum or plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Both expert and consumer panels share several important characteristics, namely (1) variation in boar taint sensitivity between people, (2) the sensory properties of skatole and androstenone and (3) the effect of cooking temperature, cooking procedure, cultural habits and meat processing on boar taint perception (Lundströ m et al, 2009). Liking or disliking of androstenone odour was found to be even more important than androstenone sensitivity in consumers' acceptance (Furnols et al, 2003).…”
Section: Introductionmentioning
confidence: 99%